Development of Diagnostic Assessment to Identify Students’ Problem Solving Abilities In Terms of Interest In Learning Mathematics - Novika Sukmaningthias; Sari, Novita; Dwi Pratiwi, Weni (Universitas Islam Ahmad Dahlan (UIAD), 2024)
This research aims to produce a diagnostic assessment instrument for identifying students' problem solving abilities in terms of their interest in learning mathematics in the form of essay questions. This research is Research & Development (R & D) research using the Tessmer development model which is known as the formative evaluation type. Tessmer development consists of 4 stages, namely preliminary, self evaluation, prototyping stage (expert reviews, one-to-one and small group) and field tests. The student response questionnaire on the diagnostic test instrument met the criteria achieved and no improvements/revisions to the test instrument will be developed because more than 70% of students gave positive responses. From the results of the student response questionnaire, it can be seen that this diagnostic test instrument product can be said to be practical to use. The results of the diagnostic test data to identify students' problem solving abilities in terms of their interest in learning mathematics, it can be seen that the number of students in the high interest in learning category, who meet the Understanding Problem indicator is 60%, the percentage of students who fulfill the Devising a Plan indicator is 50%, The percentage of students who fulfill the Carrying Out The Plan indicator is 50% and only 30% of students fulfill the Looking Back indicator. Students with a medium interest in learning category,the Understanding Problem indicator of 40%, the percentage of students who fulfill the Devising a Plan indicator is 20%, the percentage of students who fulfill the carrying out the plan indicator is 20% and only 15% of students fulfill it. looking back indicator. And in the low interest in learning category which meets the Understanding Problem indicator of 25%, the percentage of students who fulfill the devising a Plan indicator is 10%, the percentage of students who fulfill the carrying out the plan indicator is 10% and only 0% of students fulfill the looking back indicator. Based on the results of students' work in answering diagnostic tests, it can be said that this test instrument product is quite effective in identifying students' problem solving abilities in terms of their interest in learning mathematics